2013
DOI: 10.1111/jnc.12342
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic post‐conditioning facilitates brain recovery after stroke by promoting Akt/mTOR activity in nude rats

Abstract: While preconditioning is induced before stroke onset, ischemic postconditioning (IPostC) is performed after reperfusion, which typically refers to a series of mechanical interruption of blood reperfusion after stroke. IPostC is known to reduce infarction in wild type animals. We investigated if IPostC protects against brain injury induced by focal ischemia in T-cell-deficient nude rats and to examine its effects on Akt and the mammalian target of rapamycin (mTOR) pathway. Although IPostC reduced infarct size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 31 publications
2
46
1
Order By: Relevance
“…Previous studies have shown that IPostC inhibits leukocyte accumulation, IL-1β and TNF-α mRNA expression, ICAM-1 protein, IL-6, and TLR-4 as well as matrix metalloproteinase 9 (MMP9) activity (Feng et al, 2011; Liu et al, 2012; Xing et al, 2008b). Most recently, we showed that IPostC had no acute protection in T cell deficient nude rats, though it reduced brain injury measured 1 month post-stroke, suggesting that T-cell-mediated brain inflammation is involved in the protective effects of IPostC (Xie et al, 2013). We have also showed that IPostC significantly blocked increases in inflammatory cell populations in the brain, including microglia/macrophages, CD4 and CD8 T cells, as well as B lymphocytes (Joo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that IPostC inhibits leukocyte accumulation, IL-1β and TNF-α mRNA expression, ICAM-1 protein, IL-6, and TLR-4 as well as matrix metalloproteinase 9 (MMP9) activity (Feng et al, 2011; Liu et al, 2012; Xing et al, 2008b). Most recently, we showed that IPostC had no acute protection in T cell deficient nude rats, though it reduced brain injury measured 1 month post-stroke, suggesting that T-cell-mediated brain inflammation is involved in the protective effects of IPostC (Xie et al, 2013). We have also showed that IPostC significantly blocked increases in inflammatory cell populations in the brain, including microglia/macrophages, CD4 and CD8 T cells, as well as B lymphocytes (Joo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that IPostC reduces ischemic injury by inhibiting the hyperemic response and ameliorating later reduction in cerebral blood flow (CBF) and metabolism after reperfusion (Gao et al, 2008a; Ren et al, 2008), thus blocking ROS overproduction and lipid peroxidation (Abas et al, 2010), and inhibiting apoptosis (Xing et al, 2008b). IPostC also improves neuronal survival cell signaling pathways, including the Akt, mTOR and Erk pathways(Gao et al, 2008a; Pignataro et al, 2008; Xie et al, 2013). Furthermore, IPostC inhibits inflammation after stroke, as it reduces myeloperoxidase (MPO) activity, an indicator of leukocyte accumulation, attenuates IL-1β and TNF-α mRNA expression as well as ICAM-1 protein expression (Xing et al, 2008a), and blocks TLR-4 receptor expression (Feng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Akt2 knockout mice, not Akt1- and Akt3-null mice, were characterized by insulin resistance, accompanied with hyperglycemia, hyperinsulinemia and defects in insulin-dependent glucose uptake [19, 20, 21], suggesting that Akt2 is essential for insulin-dependent glucose uptake [6]. In addition, Dr. Xie et al found that pAkt2 expression in the peri-infarct area and ischemic core of brains 24 h after stroke was higher than self-controls before experimental onset in ischemic nude rats, implicating that elevated phosphorylation of Akt2 endured overnight [22]. In this study, we found that not only Akt2 mRNA but also pAkt2 Thr308 and pAkt2 Ser473 expression levels were up-regulated in the galanin and insulin groups after overnight fasting and that these levels were even higher in the insulin + galanin group compared to the galanin- or insulin-treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…38 Consistent with this pathway in poststroke recovery, ischemic postcondition has been shown to activate the AKT/mTOR pathway and stimulate an increase in axonal outgrowth, as indicated with an increase in GAP43 expression in peri-infarct regions. 39 To this end the full complement of signaling pathways that play a role in poststroke recovery, or their involvement in mechanisms associated with recovery, still remain to be full elucidated.…”
Section: Discussionmentioning
confidence: 99%